Development of an Anti-Aging Poly Herbal Cream: Exploring the effectiveness of a novel poly herbal cream for anti-aging (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this research was to create a cream that has anti-aging properties by combiningaqueous poly herbal extracts of four different plants Rosa damascena flowers (RDW), Clerodendrumpaniculatum leaves (CPW), Murraya koengii leaves (MKW), and Annona squamosa leaves (ASW). Using anenzyme-linked immunosorbent assay (ELISA), researchers were able to verify that human dermalfibroblast (HDF) cells do contain collagen-I. CB 01, CB 02, and CB 03 are the three custom blends of plantextracts that were created. Collagen-I levels were significantly higher in the extract mix (CB03) at 18.650.061ngml (p 0.05) than they were at 16.53 0.064ngml for 100gml of normal ascorbic acid. Following thedevelopment of five distinct carrier cream bases (F-1, F-2, F-3, F-4, and F-5), the optimal formulation wasfound to be F2 (PHYAAC01) with (CB03) active blend (PHYAAC02), which demonstrated a collagen-Icontent of 17.53 0.011ngml in HDF cells. Using a neutral red uptake assay using NIH3T3 cell lines, the invitro cytotoxicity of compounds (CB 03) and (PHYAAC02) was determined to be above 1000 gmL for a24-hour study period. Physical and chemical parameters, such as pH and viscosity, were used to verifythe final compositions' heat stability. Collagen-I gene expression was observed to be upregulated in theformulation (PHYAAC02) containing (CB 03) compared to the control and standard (market sample)formulations, suggesting that this ingredient may be useful for combating the ageing process andfostering the formation of a collagen matrix.